Intralimb joint coordination patterns of the lower extremity in maximal velocity phase sprint running - Gittoes, M.; Wilson, C. (Journal of Applied Biomechanics, 2010)
This study aimed to develop insight into the lower extremity joint coupling motions used in the maximal velocity phase of sprint running. Two-dimensional coordinate data were used to derive sagittal plane joint angle profiles of sprint running trials. Intralimb joint coupling motions were examined using a continuous relative phase (CRP) analysis. The knee-ankle (KA) coupling was more out of phase compared with the hip-knee (HK) coupling across the step phase (mean CRP: KA 89.9°; HK 34.2°) and produced a lower within-athlete CRP variability (VCRP) in stance. Touchdown (TD) produced more out-of-phase motions and a larger VCRP than toe-off. A destabilization of the lower extremity coordination pattern was considered necessary at TD to allow for the swing-to-stance transition. The key role that the KA joint motion has in the movement patterns used by healthy athletes in the maximal velocity phase of sprint running was highlighted.